The Responsible University Exploring the Nordic Context and Beyond - Sørensen, Mads P.; Geschwind, Lars; Kekäle, Jouni; Pinheiro, Rómulo (Springer Nature, 2019)
This book explores how the notion of the responsible university manifests itself at various levels within Nordic higher education. As the impetus of the knowledge society has catapulted the higher education sector to the forefront of policy agendas, universities and other types of higher education institutions face increasing scrutiny, assessment and accountability. This book examines this phenomenon using the Nordic countries as cases in point, given the strong public commitment towards widening participation and public research investments. The editors and contributors analyse the history and current transformations of the idea of the responsible university, investigate new innovations in the educational landscape and look into how universities have begun to organise themselves to become more responsible. Drawing together scholars from the humanities and the social sciences, this interdisciplinary collection will be of interest and value to students and scholars of the role and nature of the modern university, in addition to practitioners and policy makers tasked with finding solutions to address the competing and often contradictory demands posed by a responsibility agenda.